O jogo das aparências e as armadilhas do discurso das centrais sindicais sobre os planos de qualificação profissional - Silva, Ruteléia Cândida de Souza (2009)
This study aims at identifying in what measures the discourse performed by the Syndicate Centers related to the Professional qualification policies con substantiated in PLANFOR and PQN approaches or stays far from the group of ideas rationally planned by the state and the capital. In the field of elements that condition these policies formulation, the participation of syndicate movements in the management and execution of these plans results in a new mark for the performance of public policies and therefore in a new institutionalization for the professional constitution. In assuming this new institutionalization based on a equivalent and tripartite model that includes workers, businessmen and the government these plans take part of a wider project which aims at inserting the country into the logic of a great capital. This study, having this analytical line as a key element, shows a brief historical recovery of the Brazilian work market and concurrently rebuilds the process of constitution and syndicalism formation in the country considering its links with the state machine and with the logic of the capital. The analyses still fall on the elements of conceptual nature of PLANFOR and PNQ giving special attention to the analysis of similarities and divergences between the two plans. These are the different thematic items which provide theoretical and analytical substrates necessary to the systematization of the discourse performed by the Syndicate Centers here represented by CUT, Syndicate Force and CGTB. But, besides the historical reconstruction of the object in study, the challenge is to surpass the plan of readiness presenting the practices which neutralize the exercise of political power of workers with a critical rigorousness and which improves and intensifies the exploration of the capital over work.